The Effect of Psychoeducation on Self-Efficacy and Motivation for Taking Treatment in Breast Cancer Patients (Ca Mammae) - Hanik Endang Nihayati; Laeli Nurhanifah; Ilya Krisnana (Jurnal Ners, 2021)
Introduction: Besides being a physiological problem, breast cancer is also a psychological problem. Breast cancer patients are prone to   anxiety, depression, stress, fear, and other psychological problems. Prolonged psychological problems that are not resolved lead to impaired self-confidence and motivation to undergo treatment, which has a negative impact on health. Psychoeducation as a psychological therapy as well as providing education is used as a therapy that aims to overcome the psychological problems of breast cancer patients.Methods: This study used a quasi-experimental research design. The population in this study was breast cancer patients (ca mammae) at Prof. Dr. Margono Soekardjo Purwokerto. The sample of this study was 50 respondents obtained with purposive sampling technique. The independent variable of this study is psychoeducation and the dependent variables are self-efficacy and motivation. Data were collected using a general self-efficacy questionnaire and intrinsic motivation inventory as well as an observation sheet. Data were analyzed using the Paired T-Test and Independent Test statistical tests with a level of significance ????≤0.05.Results: There was an effect of psychoeducation to self-efficacy and motivation (p= 0.000; p=0.000.Conclusion: This study shows that psychoeducation affects self-efficacy and motivation to undergo treatment in breast cancer patients (ca mammae). Psychoeducation provides information related to breast cancer and stress management methods so that it can increase self-efficacy and motivation to undergo treatment for breast cancer patients.